Weed Control in Cole or Brassica Leafy Vegetables (Broc., Cabb., Caul., Collards, Mustard, Turnips, Kale) - William M. Stall (EDIS)
Revised! HS-189, a 5-page fact sheet by William M. Stall, describes effective weed management practices for Cole or Brassica Leafy Vegetables in Florida and provides a table of listing herbicides available to growers for chemical weed control of broccoli, cabbage, cauliflower, collards, mustard, turnips and kale. This publication updates the 2003 table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.